Shear strain gradient in Cu/Nb nanolaminates: Strain accommodation and chemical mixing. (1st August 2022) - Ma, Xiaolong; Gwalani, Bharat; Tao, Jinhui; Efe, Mert; Olszta, Matthew; Song, Miao; Yadav, Sakshi; Yu, Anqi; Nizolek, Thomas J.; Carpenter, John S.; Zhou, Bo; Devaraj, Arun; et al.
Abstract: Disentangling the intragranular and interfacial plasticity contribution to the overall strain accommodation is crucial to understanding the microstructural evolution and mass transport upon deformation in materials with the nanoscale feature size. Here, we devise a new approach to tackle the issue by introducing shear strain gradients into Cu/Nb nanolaminates of different layer thicknesses with the shear perpendicular to the laminate interfaces. The measurement of the strain gradient and the resultant lattice disorientation enables a quantitative understanding of the intragranular and interfacial plasticity contribution. We found that intragranular slip entirely governs the deformation in the 300 nm-layer laminate and, unexpectedly, contributes ∼80% of the total plasticity in the 30 nm-layer laminate. The high intragranular plasticity in the thin laminate is attributed to the large width of confined slip planes and their remnant potential for storing dislocations. In addition, substantial forced chemical mixing is observed in the top region of the 30 nm-layer laminate where the effective layer thickness is reduced below 8 nm. The transition of deformation mechanism from confined layer slip to dislocation transmission is largely responsible for the initiation of substantial mixing. Our method and findings shed light on the deformation mechanism and deformation-induced mass transport behavior in nanostructured materials. Graphical abstract: Image, graphical abstract